Sustainable Publich Health Financing dalam Perspektif Green Economy - Jasmin Ambas; Meliana Handayani; A.Ulfiana Fitri (PT. Anagata Sembagi Education, 2026)
Sustainable public health financing has become an increasingly important issue in the context of global health system resilience and sustainable development. Many countries continue to face chronic underinvestment in primary health care and increasing financial pressures due to demographic changes, environmental risks, and emerging health crises. At the same time, the concept of the green economy has gained attention as an integrated framework that connects economic development, environmental sustainability, and social well-being. This study aims to analyze sustainable public health financing from a green economy perspective by examining how green financial instruments and sustainability-oriented policies can support resilient health systems. The study employed a qualitative approach using a systematic literature review of peer-reviewed articles published between 2020 and 2025 related to public health financing, green finance, and sustainable development. The findings indicate that integrating green finance instruments, such as green bonds, climate funds, and environmental taxation, can contribute to improving environmental quality, strengthening health infrastructure, and supporting long-term public health outcomes. However, the implementation of green finance in health systems remains constrained by regulatory limitations, institutional capacity gaps, and fragmented financing structures. Therefore, integrating green economy principles into public health financing frameworks can provide strategic pathways for developing resilient, equitable, and environmentally sustainable health systems.